Proteotoxic stress in human genome stability - Santana, Inês Manuela do Vale (2014)
Incorporation of errors during protein synthesis is denominated mistranslation. This compromises the acquisition of a correct final three dimensional structure and consequently the accumulation in the cell of proteins with abnormal conformations. Cells have protein quality control (PQC) mechanisms to counteract the accumulation of aberrant proteins, but when these systems are overloaded proteins aggregate, generating proteotoxic stress. Mistranslation is associated with several diseases and with genomic alterations in yeast that increase adaptation potential. In this work, HEK293 cells were transfected with mutated tRNAs that misincorporate serine at various non-cognate codon sites. For this, a serine tRNAAGA was mutated in the anticodon and transfected into the HEK293 cells, creating five different cell lines that incorporate serine at Ala, Leu, Val, and His codons; one line was transfected with an empty plasmid (Mock). These cell lines were studied by flow cytometry and flourescence microscopy in order to evaluate their viability, proliferation, DNA content and micronuclei accumulation. The results show that mistranslation induced by these tRNAs does not affect the cellular viability but may promote minor DNA alterations. Also, cellular proliferation was compromised in some cell lines, namely in the cell line that misincorporates serine at leucine codons. In this cell line, the cell cycle was arrested in S or G2/M phases. Regarding micronuclei formation, a slight increase was seen in alanine and leucine cell lines. This cellular model allowed us to investigate the effect of low level of mistranslation on the genome of human cells and showed that human cells are highly resistant to the accumulation of aberrant proteins.